Amyloid-precursor Like Proteins APLP1 and APLP2 Are Dispensable for Normal Development of the Neonatal Respiratory Network - Han, Kang; Müller, Ulrike C.; Hülsmann, Swen (Frontiers in Molecular Neuroscience, 2017)
Recent studies using animal models indicated that the members of the amyloid precursor protein (APP) gene family are important for the formation, maintenance, and plasticity of synapses. Despite this, the specific role of the APP homologues APLP1 and APLP2 within the CNS and PNS is still poorly understood. In contrast to the subtle phenotypes of single mutants, double knockout mice (DKO) lacking APP/APLP2 or APLP1/APLP2 die within the first day after birth. Whereas APP/APLP2-DKO mice show severe deficits of neuromuscular morphology and transmission, the underlying cause of lethality of APLP1/APLP2-DKO mice remains unclear. Since expression of both proteins was confirmed by in situ hybridization, we aimed to test the role of APLP1/APLP2 in the formation and maintenance of synapses in the brainstem, and assessed a potential dysfunction of the most vital central neuronal network in APLP1/APLP2-DKO mice by analyzing the respiratory network of the medulla. We performed in vivo unrestrained whole body plethysmography in newborn APLP1/APLP2-DKO mice at postnatal day zero. Additionally, we directly tested the activity of the respiratory network in an acute slice preparation that includes the pre-Bötzinger complex. In both sets of experiments, no significant differences were detected regarding respiratory rate and cycle variability, strongly arguing against central respiratory problems as the primary cause of death of APLP1/APLP2-DKO mice. Thus, we conclude that APLP1 and APLP2 are dispensable for the development of the network and the generation of a normal breathing rhythm.